Silver Nanoparticles, Ions, and Shape Governing Soil Microbial Functional Diversity: Nano Shapes Micro - Zhai, Yujia; Hunting, Ellard R.; Wouters, Marja; Peijnenburg, Willie J. G. M.; Vijver, Martina G. (Frontiers in Microbiology, 2016)
Silver nanoparticles (AgNPs) affect microbial metabolic processes at single cell level or lab-culture strains. However, the impact of different AgNPs properties such as the particle, ion release and shape on functional responses of natural soil microbial communities remain poorly understood. As a result, we assessed the relative importance of particles and ions of AgNPs in bacterial toxicity and how the functional diversity of soil microbial communities were impacted by AgNPs shapes (i.e. plates, spheres and rods) in laboratory incubations. Our results showed that the relative contribution of AgNPs(particle) increased with increasing exposure concentrations (accounted for about 60-68% of the total toxicity at the highest exposure level). In addition, the functional composition of the microbial community differed significantly according to different AgNPs shapes. The various properties of AgNPs thus can significantly and differentially affect the functional composition of microbial communities and associated ecosystem processes depending on the level of environmental exposure.